ANALYSIS OF THE FORMATION OF TEAMWORK IN CHILDREN THROUGH DIDACTIC GAMES IN MODERN PEDAGOLOGY (SCIENCE TIME JOURNAL, 2025)
This article focuses on the fact that didactic game technologies are based on the activation and intensification of student activity, and great importance is attached to the identification and implementation of practical solutions for the realization and development of creative potential in the student.